2015
DOI: 10.1111/tct.12289
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging formative assessments of leadership for foundation doctors

Abstract: There is a wealth of evidence to highlight the importance and value of formative assessments; however, particularly for foundation doctors, these have typically been focused on assessing clinical capabilities. This HEKSS initiative encourages doctors to recognise leadership opportunities at the beginning of their careers, seeks to help them understand the importance of acquiring leadership skills and provides structured feedback to help them improve. Leadership education for doctors in training is still in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…There is a general consensus that leadership training should be incorporated into medical training of doctors; therefore, different methods to implement this must be addressed. 25 Hadley et al 9 considered whether formative assessment is a useful approach in developing the leadership skills of junior doctors and found that over 60% of those surveyed felt their leadership skills had improved as a result of feedback received. Such an approach could be transferrable to medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a general consensus that leadership training should be incorporated into medical training of doctors; therefore, different methods to implement this must be addressed. 25 Hadley et al 9 considered whether formative assessment is a useful approach in developing the leadership skills of junior doctors and found that over 60% of those surveyed felt their leadership skills had improved as a result of feedback received. Such an approach could be transferrable to medical students.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The UK is currently addressing this issue with the introduction of the MLCF and the Darzi Fellowship programmed both of which promote, train, and mentor clinicians into senior management positions. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Hadley et al’s study demonstrated that junior doctors who received formative feedback on their leadership skills felt that their skills improved as a result of said feedback. 21 Rouhani et al, as result, cited this study and suggested that this practice be transferable to medical schools. Ultimately, training must be integrated and in line with the education rather than separated and isolated from clinical instruction.…”
Section: Discussionmentioning
confidence: 77%
“…22 The basic concepts of leadership should be introduced to the medical students early in their foundation years as clinicians in leadership role have beneficial effects on health care system. 19,23 In this qualitative study perspective of house officers about "medical leadership" during their undergraduate medical education was explored in-depth because they are freshly graduated, having gone through all years of studentship and major stake holder of the health care system. It is a single centered study; the perspective of students may be different at different institutions so transferability should be considered while interpreting the results.…”
Section: Discussionmentioning
confidence: 99%